Amlodipine and Losartan Overdose Presenting with Refractory Vasodilatory Shock and Acute Kidney Injury: A Case Report - Shrestha, Utsav Kumar; Sijapati, Milesh Jung; Shrestha, Ravina Bade (Journal of Advances in Internal Medicine, 2025)
Toxicity due to calcium channel blocker overdose presents as vasodilatory shock that may be refractory to vasopressors and inotropes. Serious toxicities have also been reported with angiotensin II receptor blocker overdose, which may present as persistent refractory hypotension. The treatment options to reverse vasoplegic shock in such cases include conventional vasopressors, high dose insulin, intravenous calcium, terlipressin, and methylene blue. We report a case of a 60-year-old man who presented with decreased responsiveness following intentional ingestion of 85 mg of amlodipine and 350 mg of losartan. He was hypotensive, dyspneic and had bilateral basal crepitations at presentation. He was anuric for six hours following presentation. He was resuscitated with noradrenaline and vasopressin infusion, intravenous calcium, and high-dose insulin euglycemia therapy, highlighting the possible role of such therapies in such cases.